On the Effectiveness of Signaling Strategies in the Field of Online Investing - Friedrich Thießen; Marcel Bläute (Credit and Capital Markets – Kredit und Kapital, 2022)
The area of online investing is reshaping the financial industry through the emergence of numerous new providers with innovative concepts. This has led to new challenges for customers, such as how to assess the reliability and trustworthiness of the new providers and their offers. This empirical-experimental study has investigated the effectiveness of signaling strategies in offers for digital service innovations. The results could furnish useful input for the market strategies of the providers of innovative services. At the same time, the study serves to test theory; it can be shown that several of the usual assumptions made in the information economic based signaling theory do not apply in all cases. It is also shown that signals used by real financial service providers in the Internet are, in part, of very limited effectiveness.
Keywords: D10; D82; G41; 330; Digital Finance; FinTech; Robo Advice; Online Investing; Signaling Strategies; Market Signals; Information Economics